Eukaryote plankton assemblages in the southern Kerguelen Axis region: ecological drivers differ between size fractions - Laurence Clarke; Deagle, BE (2018)
Southern Ocean plankton communities are extremely important for global biogeochemical processes. However,recent efforts to survey marine eukaryote diversity focussed on tropical and temperate plankton communities,with limited sampling of the Southern Ocean. We used high-throughput sequencing of 18S ribosomal DNA to characterise eukaryotic diversity in 284 size-fractionated plankton samples from across the southern Kerguelen Axis, one of the most productive regions in the Indian Sector of the Southern Ocean. Based on three size fractions, combined eukaryote communities in the K-Axis region form three distinct groups, corresponding to a southern seasonal ice zone (SIZ), northern SIZ and open ocean zone. Generalised dissimilarity modelling showed that days since sea-ice melt was the key driver of community composition for the two larger size fractions (nano-and microplankton). In contrast, chlorophyll a and nitrate concentrations were better predictors for eukaryotic communities smaller than 5 μm (piconanoplankton). Other predictors varied in importance between taxonomic groups and depths, providing insights into drivers of community structure for different groups. Our results suggest that Southern Ocean eukaryotes will respond differently to environmental change depending on their taxonomy and size. Predicted changes in sea-ice extent and other environmental factors will not simply cause a shift in community location, but change the overall community composition and the suite of possible ecological interactions, with implications for trophodynamics, biogeochemistry, and carbon export.